Tindak Tutur Ekspresif dan Nilai Religiusitas dalam Animasi Nussa dan Rara pada Season 3 - Silvia Nurherawati; Agnes Apryliana; Hidayat Nur Septiadi (Pusat Riset dan Inovasi Nasional, 2024)
The problem in this research is that nowadays many children, especially teenagers, who have low character education, such as many school children, have inappropriate speaking styles because in this phase children are looking for their identity and have deviations in behavior due to a lack of application of religious values. . The aim of this research is to describe expressive speech acts and religiosity values ​​in the Nussa and Rara animation in Season 3. Qualitative methods were used in this research. The data collection techniques applied use library techniques, namely documentation techniques, listening and taking notes. This research uses Searle's theory and Glock and Strak's theory in analyzing expressive speech acts and religiosity values ​​found in the animation Nussa and Rara season 3. The conclusion of this research is that there are 6 expressive speech acts, namely praising, blaming, criticizing, complaining, apologizing and saying thank you, then other findings from this research are 5 aspects of religiosity values, namely the belief aspect, the practice aspect of worship, the experience or appreciation aspect, the knowledge aspect, and the behavioral aspect. Based on the expressive speech acts and religious values ​​contained in the Nussa and Rara season or third season animation, it can be used as a preferred means of learning Indonesian and can be implemented in daily activities.